THE EFFECTIVENESS OF PURSED LIPS BREATHING THERAPY TOWARDS KINDS' OXYGENATION STATUS WITH PNEUMONIA: DOI: https://doi.org/10.35654/ijnhs.v1i2.49 - Yunita Muliasari; Iin Indrawati (International Journal of Nursing and Health Services (IJNHS), 2018)
Background Pneumonia is the second most common disease that brings about death in children under five years of age in the world. It seems, Symptoms that appear in the case of Pneumonia are acute respiratory problems that need to be overcome appropriately. Objectives the aim of this research is to identify the effect of pursed lips breathing therapy through tongue blowing activity on the oxygenation status of preschoolers with Pneumonia. Method this research used quasi experimental with pre-post test group design. The sampling technique is purposive random sampling with 36 people consisting of 18 intervention groups and 18 control groups. Data were analyzed using univariate and bivariate tests (t-test) Result The results showed a significant difference between oxygenation status before and after intervention with tongue blowing therapy (PLB), namely p value= 0.045 on respiratory frequency (RR), p value = 0.037 to saturation oxygen (Sa02) and p value=0.036 on heart rate (HR). Recommendation The results of this study can add alternatives to independent nurse interventions in dealing with pediatric patients who have pneumonia or with oxygenation disorders.